Advertisement

Report

rtodd588Follow

Jan. 27, 2023•0 likes## 0 likes

•3 views## views

Be the first to like this

Show More

Total views

0

On Slideshare

0

From embeds

0

Number of embeds

0

Upcoming SlideShare

Factoring if a is greater than 1 grade8

Loading in ... 3

Jan. 27, 2023•0 likes## 0 likes

•3 views## views

Be the first to like this

Show More

Total views

0

On Slideshare

0

From embeds

0

Number of embeds

0

Download to read offline

Report

Education

help me solve this equation 2/2x-3/x plus 3=1 please Solution Subtracting three on both sides we will get 2/2x-3/x = -2................1) Find the common denominator term and subtract the given function. we will get the common denominator as 2x^2 now, turn the given fraction into its equivalent term 2/2x = multiplying x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 2/2x = 2x/2x^2 and for 3/x = multiplying 2x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 3/x = (3 * 2x)/2x^2 = 6x/2x^2 now, replace the fraction of equation 1 with its equivalent one we will get.. 2x/2x^2 - 6x/2x^2 = -2 (2x - 6x)/2x^2 = -2 -4x/2x^2 = -2 -2/x = -2 x = 1 .

rtodd588Follow

Advertisement

- help me solve this equation 2/2x-3/x plus 3=1 please Solution Subtracting three on both sides we will get 2/2x-3/x = -2................1) Find the common denominator term and subtract the given function. we will get the common denominator as 2x^2 now, turn the given fraction into its equivalent term 2/2x = multiplying x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 2/2x = 2x/2x^2 and for 3/x = multiplying 2x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 3/x = (3 * 2x)/2x^2 = 6x/2x^2 now, replace the fraction of equation 1 with its equivalent one we will get.. 2x/2x^2 - 6x/2x^2 = -2 (2x - 6x)/2x^2 = -2 - 4x/2x^2 = -2 -2/x = -2 x = 1

Advertisement